Effectiveness of executive function training on mental set shifting, working memory and inhibition in healthy older adults: A double‐blind randomized controlled trials. (24th January 2018) - Chiu, Huei‐Ling; Chan, Pi‐Tuan; Kao, Ching‐Chiu; Chu, Hsin; Chang, Pi‐Chen; Hsiao, Shu‐Tai Sheen; Liu, Doresses; Chang, Wen‐Chi; Chou, Kuei‐Ru
Abstract: Aims: The aim of this study was to evaluate the effectiveness of executive function training on mental set shifting, working memory and inhibition for healthy older adults. Background: Executive functions control and guide individuals' behaviours through a top‐down cognitive model and have been regarded as the exhibition and integration of various high‐level cognitive functions. However, prior studies have rarely focused on the subcomponent indicators of executive function, such as mental set shifting, working memory and inhibition in healthy older adults. Design: Randomized controlled trial. Methods: A total of 62 participants were recruited between January 2015 ‐ March 2017, with both groups attending a 30‐min training session three times per week for 8 weeks. Executive function training group received the training content that focused on the mental set shifting, working memory and inhibition. Active control group engaged in passive information activities. The primary outcome was mental set shifting, measured by the Wisconsin card sort test. The secondary outcomes were working memory measured by digit span and inhibition measured by the Stroop color word test. Results: The executive function training group had statistically significant higher scores of mental set shifting and working memory at immediate follow‐up and that its effect on mental set shifting could be maintained for 3–6 months. However, this training did not have any statistically significant results on inhibition. Conclusion: The executive function training may be an effective preventive intervention for healthy older adults. Future studies are recommended to include a broader range of participants with different levels of cognitive function.